MITIGASI BENCANA GEMPA MELALUI PERKUATAN KOMPONEN STRUKTURAL DAN NON-STRUKTURAL PADA RUMAH TINGGAL: DISASTER MITIGATION OF EARTHQUAKES THROUGH STRENGTHENING OF STRUCTURAL AND NON-STRUCTURAL COMPONENTS OF RESIDENTIAL HOMES - BADZLINA NESYA; MONIKA NATALIA; ZULFIRA MIRANI; LILIS NOVITASARI; MICKY FETRIANI (LPPM Universitas Abdurrab, 2025)
The damage caused by earthquakes can be minimized by planning and constructing earthquake-resistant buildings. In efforts to mitigate earthquake risk, residential houses must be built with earthquake reinforcement, by adding seismic reinforcement to structural components (foundations, beams, columns) and non-structural components (walls, roofs). The addition of earthquake reinforcement features to housing only adds 5% to the total implementation cost, which is very small compared to the risks that will be faced. The earthquake reinforcement features are applied based on the Technical Guidelines for Earthquake Resistant Houses and Buildings (Directorate General of Cipta Karya and the Department of Public Works) number 5 of 2006, SNI 1726-2019 regarding Procedures for Earthquake Resistance Planning for Building Structures and Non-Building Structures, as well as SNI 1727:2020 regarding minimum design loads and related criteria for buildings and other structures. With the knowledge and skills acquired, it is hoped that the partners will be able to directly apply them to the houses they will build as an effort to mitigate earthquakes and minimize risks and losses that may occur. The objectives to be achieved from this community service activity are: partners to understand the features of earthquake reinforcement in residential homes; partners to acquire skills and training in the methods of creating earthquake-safe dwellings; partners to apply this in the housing they build. The method to be employed in this activity will include field surveys, counseling/socialization, and technical training for the application of earthquake reinforcement on structural components (foundations, beams, columns) and non-structural components (walls, roofs). This activity was attended by 13 participants, with the success identified based on the level of understanding absorbed during the socialization in the discussion session.